Pengaruh Word Of Mouth, Kualitas Layanan, Kualitas Produk Dan Lokasi Terhadap Keputusan Pembelian Konsumen (Studi pada Cafe Maitreya Kopi Dau Malang) - Zaidanil Kamil; Abdul Kodir Djaelani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of word of mouth, service quality, product quality and location on consumer purchasing decisions (Case Study at Cafe Maitreya Kopi Dau Malang). The variables used in this study, namely the purchase decision variable (dependent variable), while the independent variables are word of mouth, service quality, product quality and location.The results of this study partially conclude that the variables are word of mouth, service quality, product quality and location. there is a significant influence on purchasing decisions and simultaneously concludes that there is a significant influence between the variables word of mouth, service quality, product quality and location on purchasing decisions. Keywords: Word Of Mouth, Service Quality, Product Quality And Location, Purchase Decision